Hans Jonas: The principle of responsibility and the nuclear weapons - Alvarado Ramos, Jonathan Eduardo (2022)
In the present work, the ethical concepts of Jonas are analyzed: the principle of responsibility and the new imperative and their discussion with the use of nuclear weapons. Therefore, the notions of technique (techne), nature (physis) and modern technique will be described. In these descriptions it will be possible to appreciate the extension of the power of modern technology and the possible negative repercussions that it could have against the possibility of the conservation of human life and nature. Thus, the use and possession of nuclear weapons will be taken as a matter of ethical questioning.